The prevention, screening and treatment of congenital heart block from neonatal lupus: a survey of provider practices. (18th August 2018) - Clowse, Megan E B; Eudy, Amanda M; Kiernan, Elizabeth; Williams, Matthew R; Bermas, Bonnie; Chakravarty, Eliza; Sammaritano, Lisa R; Chambers, Christina D; Buyon, Jill
Abstract: Objective: To survey an international sample of providers to determine their current practices for the prevention, screening, and treatment of congenital heart block (CHB) due to maternal Ro/SSA antibodies. Methods: A survey was designed by the organizing committee of the 9th International Conference of Reproduction, Pregnancy and Rheumatic Diseases. It was sent to attendants of the conference and authors of recent publications or abstracts at ACR 2012, 2013 or 2014 on rheumatic diseases and pregnancy. Results: In anti-Ro/SSA positive women, 80% of 49 respondents recommended screening by serial fetal echocardiogram (ECHO), with most starting at week 16 (59%) and stopping at week 28 (25%), although the time to stop varied widely. For women without a prior infant with neonatal lupus, respondents recommend every other week (44%) or weekly (28%) fetal ECHOs. For women with a prior infant with neonatal lupus, 80% recommend weekly fetal ECHOs. To prevent CHB, HCQ was recommended by 67% of respondents and most would start pre-pregnancy (62%). Respondents were asked about medications to treat varying degrees of CHB in a 20-week pregnant, anti-Ro and La positive SLE patient. For first degree, respondents recommended starting dexamethasone (53%) or HCQ (43%). For second degree, respondents recommended starting dexamethasone (88%). For third degree, respondents recommended starting dexamethasone (55%) or IVIg (33%), although 27% would not start treatment. Conclusion: Despite the absence of official guidelines, many physicians with a focus on pregnancy and rheumatic disease have developed similar patterns in the screening, prevention and treatment of CHB.